Role of diversification rates and evolutionary history as a driver of plant naturalization success - Lenzner, Bernd; Magallón, Susana; Dawson, Wayne; Kreft, Holger; König, Christian; Pergl, Jan; Pyšek, Petr; Weigelt, Patrick; van Kleunen, Mark; Winter, Marten; Dullinger, Stefan; Essl, Franz (The New phytologist, 2021)
Human introductions of species beyond their natural ranges and their subsequent establishment are defining features of global environmental change. However, naturalized plants are not uniformly distributed across phylogenetic lineages, with some families contributing disproportionately more to the global alien species pool than others. Additionally, lineages differ in diversification rates, and high diversification rates have been associated with characteristics that increase species naturalization success. Here, we investigate the role of diversification rates in explaining the naturalization success of angiosperm plant families. We use five global data sets that include native and alien plant species distribution, horticultural use of plants, and a time-calibrated angiosperm phylogeny. Using phylogenetic generalized linear mixed models, we analysed the effect of diversification rate, different geographical range measures, and horticultural use on the naturalization success of plant families. We show that a family's naturalization success is positively associated with its evolutionary history, native range size, and economic use. Investigating interactive effects of these predictors shows that native range size and geographic distribution additionally affect naturalization success. High diversification rates and large ranges increase naturalization success, especially of temperate families. We suggest this may result from lower ecological specialization in temperate families with large ranges, compared with tropical families with smaller ranges.
Keywords: rostliny; alien species; evolution; Geography; invasion success; ekosystém; zavlečené druhy; zeměpis; geographic distribution; Ecosystem; fylogeneze; Introduced Species; Phylogeny; plant naturalization; Plants; range size